Cyberchondria: a Growing Concern During the COVID-19 Pandemic and a Possible Addictive Disorder? - Mestre-Bach, Gemma; Potenza, Marc N. (Current Addiction Reports, 2023)
Purpose of Review: The main purpose of this narrative review is to provide a brief overview of the current empirical evidence regarding the conceptualization, assessment, and treatment of cyberchondria, with a focus on the potential classification of cyberchondria as a behavioral addiction. Although cyberchondria has been widely associated with anxiety, it has also been suggested that it may be linked to obsessive–compulsive features. A less explored proposal is the categorization of cyberchondria as a behavioral addiction. The present review explores the existing literature with respect to the possible classification of cyberchondria as a behavioral addiction by considering cyberchondria with respect to components of the interaction of person, affect, cognition and execution model. Recent Findings: There is a lack of consensus regarding the definition and conceptualization of cyberchondria. The empirical evidence available to date suggests that cyberchondria is a multifactorial construct that operates transdiagnostically, particularly with respect to obsessive–compulsive-related disorders and health-related anxiety. The extent to which the condition may reflect a behavioral addiction as a form of problematic use of the internet also warrants consideration. Cyberchondria may have become more prevalent during the COVID-19 pandemic, with particular populations prone to health-related anxiety likely having greater vulnerability. Existing data in part support the potential classification of cyberchondria as a behavioral addiction, although many gaps in understanding currently exist. Summary: Cyberchondria appears to be a growing concern. However, there is not yet enough empirical evidence to determine whether this clinical condition has enough similarities with behavioral addictions to be considered as one. Likewise, psychometric instruments that exist to date have not been designed from the theoretical framework of behavioral addictions, so most of the factors that they evaluate may be preferentially related to anxiety. Finally, there is still no consensus on whether cyberchondria should be addressed in the context of health anxiety interventions, OCRD, or behavioral addictions; thus, more empirical evidence is needed.
Keywords: addictive behaviors; assessment; compulsive behaviors; COVID-19; cyberchondria; treatment; Scopus; JCR